National And Public Interest Perspective on the Governance and Regulation of Carbon Capture and Storage Implementation in Indonesia - Sasono Setyadi, Didik; Renny See , Benedictus; Bimo Utomo , Ario (Action Research Literate, 2024)
Recently Indonesian Government issued two important regulations regarding Carbon Capture Storage (CCS) namely, President Regulation No. 14/2024 and Ministry of Energy and Mineral Resources Regulations No. 2/2003. Both regulations have caused Indonesia's CCS Legal and Regulatory score by the Global CCS Institute to increase significantly. There are three criteria applied by the Global CCS Institute to define the score: regulation of trans boundaries movement of CCS, specific legal and regulatory framework, and facilitation of early project. Despite the increase in CCS score, some essential questions remain as crucial problems that are not solvable easily. Those questions regarding the national and common interest of Indonesian people by the issuance of both legal and regulations are still unclear, at least from the common people's perspective. The Presidential Regulation define dual schemes for CCS implementation: Contract Scheme and Permit Scheme. From the common people's perspective, both schemes need to be exercised further to respond to the public questions properly. Therefore, any reason behind the implementation of those two schemes as well as any potential benefit for Indonesia by implementing those two schemes in parallel are very important to be reviewed and analyzed. Reinforcement of Oil and Gas Production Sharing Contract Principles in the implementation of CCS in Indonesia are more favourable for the National and Public Interest Perspective.